Growth and development of children under 2 at a healthcare center in Yasooj - Safari, M; Soleimani, M; Ashkoo, M; Sayad, F (Advances in Nursing & Midwifery, 2010)
Background and aim One of the reliable criteria for evaluating health status of children is appropriate growth and development particularly in the first 2 years of life. This descriptive study was carried out to determine the patterns of growth and development of children under 2 and some related factors brought to Shahid Shafiee Health Center at Yasooj (a city in Iran) in 2007. Materials and methods 225 children brought by their parents for health checkups were selected through convenience sampling. A questionnaire was completed by interviewing with their mothers and an examination form was used to document weight, height and head circumference of children. Different statistical tests such as independent t, Chi-square and one-way ANOVA were used for data analysis. Data were analyzed by SPSS 15. Findings 108 subjects (%48) were female and the rest (%52) was male (SD=9.4±5.5). %65.8 was born through vaginal delivery while %34.2 with caesarian. %75.1 was breast-fed. Mean birth weight was 3071.6±517.7 gm. No significant difference was found between means and standard deviations of weight, height as well as head circumferences between girls and boys. Such developmental indices as means of age for neck holding, sitting, tooth growing, standing and walking were 3.5±1.5, 7.6±2, 9.7±1.8 and 10.9±2 months respectively. In all age groups, the medians of weight and height for age were less than National Center of Health Statistics (NCHS) standards with less difference between 0-6 months and more difference between 1-2 years. Growth patterns of children had a significant relationship with the type of birth and occupation of their fathers (p<0.05). Conclusion Lower growth and development indices from international standards may be due to unsuitable environmental as well as health conditions and malnutrition. Lower difference of the indices from the standards in infants before 6 months may be attributed to the role of breast milk as the primary food at this age. Keywords: Growth and development, Infants, Related factors. *Corresponding Author: Mitra, Safari. Lecturer, Dept. of Midwifery, Faculty of Nursing and Midwifery, Yasooj University of Medical Sciences. Yasooj, Iran. E-mail: mitra_safari39@yahoo.com